Understanding planting preferences – A case-study of the afforestation choices of farmers in Ireland. (April 2022) - Ryan, Mary; O'Donoghue, Cathal; Hynes, Stephen; Jin, Yan
Abstract: The importance of forests in the provision of ecosystem services that provide multiple benefits to society is increasingly being recognised. These services include climate change and greenhouse gas (GHG) mitigation, water quality protection, fibre for timber processing or wood energy and recreation opportunities. However, afforestation targets across Europe are not being met, despite the availability of planting subsidies in some countries. Using Ireland as a case study, this paper uses a novel technique to examine the afforestation participation decision utilising a choice modelling framework, where a revealed preference methodology is applied to the land use change from agriculture to forestry at individual farm level for the first time. The model coefficients are consistent with economic theory relative to the utility maximisation of income, leisure and wealth (long term land value) and suggest that while income is a key driver of the participation decision at individual farm level, the non-pecuniary benefits from farming are also a consideration. Highlights: Discrete choice modelling is advanced by estimating structural parameters for the planting decision on individual farms. A dataset incorporating policy and economic variability enables the quantification of the utility function for farm forestry. The quantitative analytical method confirms theoretical perspectives in relation to financial drivers in a formal manner. However, results also confirm the importance of non-financial drivers of planting decisions. The framework has potential for use in other life-cycle decisions on farms, forests and other land use choices.